2005
DOI: 10.1111/j.1525-1314.2005.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

An Early Palaeozoic HP/HT granulite–garnet peridotite association in the south Altyn Tagh, NW China:P–Thistory and U‐Pb geochronology

Abstract: High-pressure kyanite-bearing felsic granulites in the Bashiwake area of the south Altyn Tagh (SAT) subduction-collision complex enclose mafic granulites and garnet peridotite-hosted sapphirine-bearing metabasites. The predominant felsic granulites are garnet + quartz + ternary feldspar (now perthite) rocks containing kyanite, plagioclase, biotite, rutile, spinel, corundum, and minor zircon and apatite. The quartz-bearing mafic granulites contain a peak pressure assemblage of garnet + clinopyroxene + ternary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 49 publications
4
94
0
1
Order By: Relevance
“…443-423 Ma;Chen et al, 2007Chen et al, , 2009Zhang et al, 2008;Song et al, 2006;Yu et al, 2013), the South Altyn (ca. 501-485 Ma; Zhang et al, 2005;Liu et al, 2012;Cao et al, 2013), the North Qinling orogen (ca. 511-480 Ma; Liu et al, 2010;Zhang et al, 2011;Cheng et al, 2011Cheng et al, , 2012Wang et al, 2011;ca.…”
Section: Early Palaeozoic Hp/uhp Metamorphism In Gondwana-derived Termentioning
confidence: 99%
See 1 more Smart Citation
“…443-423 Ma;Chen et al, 2007Chen et al, , 2009Zhang et al, 2008;Song et al, 2006;Yu et al, 2013), the South Altyn (ca. 501-485 Ma; Zhang et al, 2005;Liu et al, 2012;Cao et al, 2013), the North Qinling orogen (ca. 511-480 Ma; Liu et al, 2010;Zhang et al, 2011;Cheng et al, 2011Cheng et al, , 2012Wang et al, 2011;ca.…”
Section: Early Palaeozoic Hp/uhp Metamorphism In Gondwana-derived Termentioning
confidence: 99%
“…Close faunal affinities suggest contiguity of these continental blocks with each other and with Gondwana from the Cambrian to the Silurian (Rong et al, 1995). Considering the paleogeographic framework of eastern Gondwana, early Paleozoic metamorphic rocks, especially the ultrahigh/high- Chen et al, 2007Chen et al, , 2009Zhang et al, 2008;Song et al, 2006;Yu et al, 2013), the South Altyn (501-485 Ma; Zhang et al, 2005;Liu et al, 2012;Cao et al, 2013), the North Qinling orogen (ca. 511-480 Ma, Liu et al, 2010;Zhang et al, 2011;Wang et al, 2011;Cheng et al, 2011Cheng et al, , 2012ca.…”
Section: Early Palaeozoic Hp/uhp Metamorphism In Gondwana-derived Termentioning
confidence: 99%
“…It has been correlated to the south Altyn Tagh HP/UHP metamorphic terrane, and constrains a 400 km offset for the Altyn Tagh fault. Therefore, South Altyn-North Qaidam was considered as a single HP-UHP metamorphic belt truncated by a large strike-slip fault, similar to the case of the Dabie-Sulu HP-UHP metamorphic zone which was truncated by the sinistral Tanlu strike-slip fault in eastern China, and split into the Dabie and Sulu regions [14][15][16][17][18][19][20][21] . However, in contrast to Dabie-Sulu in eastern China, where UHP metamorphic evidence has been commonly recognized in different rock types, evidence of UHP metamorphism is relatively rare in the north Qaidam (NQD) and south Altyn Tagh (SAT) [11,22,23] .…”
mentioning
confidence: 99%
“…During the past ten years, various HP-UHP metamorphic rocks have been discovered in the South Altyn Tagh, the North Qaidam and the North Qinling (Yang and Powell, 2008;Liu et al, 2007aLiu et al, , 2004aLiu et al, , b, 2003aLiu et al, , b, 2002Liu et al, , 2001Liu et al, , 1997Liu et al, , 1996aSong et al, 2006Song et al, , 2005aSong et al, , b, 2004Song et al, , 2003aYang J S et al, 2003Yang J S et al, , 2002aYang J S et al, , b, 2001Yang J S et al, , 2000Yang J S et al, , 1998Zhang J X et al, 2005aZhang J X et al, , 2002Zhang J X et al, , 2001Zhang J X et al, , 1999Song and Yang, 2001;Liu, 1999;Liu and Zhou, 1995;Yang J J et al, 1994;). They were believed to be the products of deep subduction of continental crusts in the Early Paleozoic.…”
Section: Important Progressmentioning
confidence: 97%
“…Grt+Ol (olivine)+Opx+Cpx±Mgs (magnisite) is the peak-stage metamorphic mineral assemblage of garnet lherzolite, and peak P-T conditions are estimated at 3.8-5.1 GPa and 880-970 using garnet ℃ -orthopyroxene barometer and garnet-clinopyroxene Fe-Mg exchange thermometer (Liu et al, 2002). Subsequently, Zhang et al (2005a) thought that the garnet lherzolite, Grt clinopyroxenite and granitic gneiss in Yinggelisayi underwent HP/UHT metamorphism owing to the discovery of sapphirine-bearing metabasites which occur as mafic layers in the garnet peridotite. Wang et al (in review) reported that the Yinggelisayi garnet peridotites have the records of an early transformation from spinel peridotite into garnet peridotite (peak stage at 4.2-6.0 GPa and 920-990 ℃), a latter transformation into amphibole garnet peridotite and a final transformation into spinel peridotite (Fig.…”
Section: South Altyn Taghmentioning
confidence: 99%